Experience on healthcare utilization in seven administrative regions of Tanzania - Kayombo Edmund J; Uiso Febronia C; Mahunnah Rogasian LA (BMC, 2012)
Abstract Health care utilization in many developing countries, Tanzania included, is mainly through the use of traditional medicine (TRM) and its practitioners despite the presence of the conventional medicine. This article presents findings on the study that aimed to get an experience of health care utilization from both urban and rural areas of seven administrative regions in Tanzania. A total of 33 health facility managers were interviewed on health care provision and availability of supplies including drugs, in their respective areas. The findings revealed that the health facilities were overburden with higher population to serve than it was planned. Consequently essential drugs and other health supplies were available only in the first two weeks of the month. Conventional health practitioners considered traditional health practitioners to be more competent in mental health management, and overall, they were considered to handle more HIV/AIDS cases knowingly or unknowingly due to shear need of healthcare by this group. In general conventional health practitioners were positive towards traditional medicine utilization; and some of them admitted using traditional medicines. Traditional medicines like other medical health systems worldwide have side effects and some contentious ethical issues that need serious consideration and policy direction. Since many people will continue using traditional/alternative medicine, there is an urgent need to collaborate with traditional/alternative health practitioners through the institutionalization of basic training including hygiene in order to improved healthcare in the community and attain the Millennium Development Goals by 2015.